"A Mile in Her Shoes": A qualitative exploration of the perceived benefits of volunteer led running groups for homeless women. (21st April 2019) - Dawes, Jo; Sanders, Charlotte; Allen, Rebecca
Abstract: "A Mile in Her Shoes" is a volunteer‐led charity which provides running groups for homeless women. The objective of this study was to explore the experiences of homeless women attending these running groups and to establish how participation in a supported running group impacted their lives. This exploratory qualitative study was carried out across two sites in London UK during February and April 2017. All regular attenders of the running groups were invited to participate in the study; subsequently, a self‐selected sample of 11 women consented to being interviewed. Data were collected by female interviewers on a one‐to‐one basis, steered by a semi‐structured topic guide. All interviews were digitally recorded, transcribed verbatim, and analysed using thematic analysis. Themes were cross‐referenced by the research team and findings were supported by direct quotes. Five main themes emerged from the findings: the positive impact of the charity; homeless women's motivations and barriers to participating in running groups; the benefits of participating on physical and mental health; the importance and value of social support from the group; and the value of being provided with quality running kit. This study concludes that volunteer‐led running groups are valued by homeless women by helping them take control of their health. It provides insight into their engagement in physical activity, thus potentially helping prevent injury or illness, and aiding recovery and rehabilitation. One implication of this study is that gathering homeless women's views helps to steer how community‐based physical activity programmes can benefit their wellbeing. However, this small‐scale study may have limited generalisability, with the topic warranting further research.